Implementation of the Internal Control System (ICS) in the Provincial Municipality of Acobamba, 2019-2022 - Quispe Sullcaray, Yoni (2025)
Objective: The present study aimed to determine the level of implementation Internal Control System (ICS) in the Provincial Municipality of Acobamba, Peru, 2019-2022. Materials and methods: The study was of descriptive type, of design non-experimental, and cross-sectional. Having as an object of study to the Provincial Municipality of Acobamba. To collect data, the technique of document analysis was used, using published data for this purpose by the Comptroller General of the Republic (CGR) in the query application for deliverables for the implementation of the SCI in public entities of the State. That comes from information the information generated and recorded by the entity with the implementation of the SCI. The study population was of data from all years in which the level of SCI implementation was measured in the study entity. The sample was of data on the level of SCI implementation during the 2019-2022 period. Results: The results evidence that the SCI level achieved by the study entity in 2019 was non-existent (0.00%), in 2020 it was intermediate (67.24%), in 2021 it was intermediate (66.38%), and in 2022 it was intermediate (70.18%). Conclusions: It is concluded that the level of implementation of the SCI in the Provincial Municipality of Acobamba in the study period is found below the ideal level required by the CGR, that should be greater than 90.00%.